PENGARUH LITERASI KEUANGAN TERHADAP MINAT I NVESTASI DI PASAR MODAL PADA GENERASI Z (STUDI KASUS MAHASISWA PENDIDIKAN EKONOMI ANGKATAN 2018 FKIP ULM) - Raden Gilang Kresna Bayu; Ni Nyoman Suarniki; Lusiana Pratiwi (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
The aim of the research is to find out the Effect of Financial Literacy on Investment Interest in the Capital Market in Generation Z (Case Study of Economics Education Students Class of 2018 FKIP ULM) The research method used is a quantitative descriptive method. The population of this study were Economics Education Students Class of 2018 FKIP ULM. The sample is 80 respondents. Multiple linear regression data analysis technique with the SPSS version 22 program. The results of the study show that financial literacy which consists of knowledge, abilities and beliefs shows the result that knowledge and beliefs have a partial positive effect on the investment interest of Economics Education students Batch of 2018 FKIP ULM. Whereas financial literacy which consists of knowledge, abilities and beliefs has a positive effect simultaneously on the investment interest of Economics Education students Batch 2018 FKIP ULM.